Relationships, happiness and well-being: insights from Bangladesh - Camfield, L; Choudhury, K; Devine, J (Wellbeing in Developing Countries Research Group, University of Bath, 2006)
Although Bangladesh is known as one of the poorest and most densely populated countries in the world, its people seem to enjoy levels of happiness that are higher than those found in many other countries. This includes ‘developed’ countries where people have larger per capita incomes and can access a wider range of public services and goods. The paper explores this apparent paradox by analysing primary quantitative and qualitative data, and engaging with existing literature on happiness and objective wellbeing in Bangladesh. The data and analysis presented here contributes to the limited knowledge we have of the construction and experience of happiness and life satisfaction in contexts of extreme and persistent economic poverty. It identifies and offers insights into the ‘personal’ as well as social or ‘relational’ values and goals that people in Bangladesh consider important to achieve happiness in life. This, we argue, leads to a better understanding of the role of social and cultural context in the construction of people’s happiness. In the conclusion, we reflect on the policy implications of our findings.